2014
DOI: 10.1017/s1431927613014001
|View full text |Cite
|
Sign up to set email alerts
|

EBSD Analysis of Tungsten-Filament Carburization During the Hot-Wire CVD of Multi-Walled Carbon Nanotubes

Abstract: Filament condition during hot-wire chemical vapor deposition conditions of multi-walled carbon nanotubes is a major concern for a stable deposition process. We report on the novel application of electron backscatter diffraction to characterize the carburization of tungsten filaments. During the synthesis, the W-filaments transform to W2C and WC. W-carbide growth followed a parabolic behavior corresponding to the diffusion of C as the rate-determining step. The grain size of W, W2C, and WC increases with longer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Additionally, Figure (b) shows a dark contrast region above the SiN x layer that is due to nanometer scale material from the filament depositing at the initial stage of diamond deposition. This filament material is known to occur in HFCVD diamond, and the details of this phenomena will be discussed in a separate report.…”
Section: Results and Discussionmentioning
confidence: 97%
“…Additionally, Figure (b) shows a dark contrast region above the SiN x layer that is due to nanometer scale material from the filament depositing at the initial stage of diamond deposition. This filament material is known to occur in HFCVD diamond, and the details of this phenomena will be discussed in a separate report.…”
Section: Results and Discussionmentioning
confidence: 97%
“…Under different power conditions, the higher the power, the more heat the filament provides (Figure 9a). Zeiler et al [ 27 ] investigated the changes in tungsten filaments during diamond CVD and found the first‐step W‐to‐W 2 C phase transformation. The methane dissociation at the W filament surface was the rate‐determining step.…”
Section: Resultsmentioning
confidence: 99%
“…One can avoid this problem using HFCVD and DC electrical discharge systems with more uniform temperature distribution [3,[10][11][12] to produce diamond films on complex shape substrates. However, there are technical difficulties because of filament carburization [13], moreover, typical growth rates in the HFCVD method are by an order of magnitude lower compared to that for MPCVD [14]. The heating uniformity becomes to be a problem upon MPCVD deposition scaling.…”
Section: Introductionmentioning
confidence: 99%